Provenance, transport and diagenesis of sediment in polar areas: a case study in Profound Lake, King George Island, Antarctica - Hernández, Ana C; Bastias, Joaquin; Matus, Daniela; Mahaney, William C (Polar Research, 2018)
Detailed scanning electron microscopy (SEM) micro-texture and mineralogical analysis of lacustrine sediment recovered from Profound Lake (also known as Uruguay Lake), Antarctica, was conducted in the foreland area of the Collins Glacier, King George Island. Very coarse and coarse sand grade size fractions (2 mm – 600 μm) were examined with SEM/ energy dispersive spectrometry, while the total sand fraction and fines (silt + clay) were examined using x-ray diffraction to determine relationships to source rock, weathering and transport history and long-term clay mineral weathering, all of which are poorly understood in polar areas. The mineralogy of these sediments was compared with petrographical information of the country rock to identify potential detrital sources. The association of recovered detrital minerals, sometimes strongly pre-weathered, supports release from source rock of basaltic and andesitic compositions. The micro-texture analysis of quartz, magnetite and various plagioclase grains show micro-features that reveal a complex weathering–diagenesis history tentatively extending into the Paleogene. The bedrock was eroded mostly by glacial processes and mechanical action presumed to result from glacial crushing. Alteration minerals, likely the product of pre-weathering, are probably sourced from weathered bedrock during contact with the sub-aerial atmosphere prior to entrainment. However, amorphous silica precipitation indicates weathering subsequent to glacial erosion from the source bedrock. Cracks of variable dimensions are mostly characteristic of either frost weathering or glacial transport, and involve mechanical and chemical processes.
Keywords: Antarktis; geologi; mineralogi; petrografi; polarområdene; sedimentologi

Transpression and tectonic exhumation in the Heimefrontfjella, western orogenic front of the East African/Antarctic Orogen, revealed by quartz textures of high strain domains - Bauer, Wilfried; Siemes, Heinrich; Spaeth, Gerhard; Jacobs, Joachim (Polar Research, 2016)
The metamorphic basement of the Heimefrontfjella in western Dronning Maud Land (Antarctica) forms the western margin of the major ca. 500 million year old East African/East Antarctic Orogen that resulted from the collision of East Antarctica and greater India with the African cratons. The boundary between the tectonothermally overprinted part of the orogen and its north-western foreland is marked by the subvertical Heimefront Shear Zone. North-west of the Heimefront Shear Zone, numerous low-angle dipping ductile thrust zones cut through the Mesoproterozoic basement. Petrographic studies, optical quartz c-axis analyses and x-ray texture goniometry of quartz-rich mylonites were used to reveal the conditions that prevailed during the deformation. Mineral assemblages in thrust mylonites show that they were formed under greenschist-facies conditions. Quartz microstructures are characteristic of the subgrain rotation regime and oblique quartz lattice preferred orientations are typical of simple shear-dominated deformation. In contrast, in the Heimefront Shear Zone, quartz textures indicate mainly flattening strain with a minor dextral rotational component. These quartz microstructures and lattice preferred orientations show signs of post-tectonic annealing following the tectonic exhumation. The spatial relation between the sub-vertical Heimefront Shear Zone and the low-angle thrusts can be explained as being the result of strain partitioning during transpressive deformation. The pure-shear component with a weak dextral strike-slip was accommodated by the Heimefront Shear Zone, whereas the north–north-west directed thrusts accommodate the simple shear component with a tectonic transport towards the foreland of the orogen. Keywords: Dronning Maud Land; quartz microfabrics; X-ray texture goniometry; shear zones; mylonites.
Keywords: Dronning Maud Land; geologi; mylonitter; petrografi; tektonikk

The Main Shear Zone in Sør Rondane, East Antarctica: Implications for the late-Pan-African tectonic evolution of Dronning Maud Land - Ruppel, Antonia S; Läufer, Andreas; Jacobs, Joachim; Elburg, Marlina; Krohne, Nicole; Damaske, Detlef; Lisker, Frank (Tectonics, 2015)
Structural investigations in western Sør Rondane, eastern Dronning Maud Land (DML), provide new insights into the tectonic evolution of East Antarctica. One of the main structural features is the approximately 120 km long and several hundred meters wide WSW-ENE trending Main Shear Zone (MSZ). It is characterized by dextral high-strain ductile deformation under peak amphibolite-facies conditions. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between late Ediacaran to Cambrian times (circa 560 to 530 Ma). The MSZ separates Pan-African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the north from a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite complex with “Indo-Antarctic” affinities in the south. It is interpreted to represent an important lithotectonic strike-slip boundary at a position close to the eastern margin of the East African-Antarctic Orogen (EAAO), which is assumed to be located farther south in the ice-covered region. Together with the possibly coeval left-lateral South Orvin Shear Zone in central DML, the MSZ may be related to NE directed lateral escape of the EAAO, whereas the Heimefront Shear Zone and South Kirwanveggen Shear Zone of western DML are part of the south directed branch of this bilateral system.
Keywords: Dronning Maud Land; geokronologi; geologi; geovitenskap; petrografi; tektonikk

Flood Basalts of Vestfjella: Jurassic Magmatism Across an Archaean–Proterozoic Lithospheric Boundary in Dronning Maud Land, Antarctica - Luttinen, Arto V.; Furnes, Harald (Journal of Petrology, 2000)
Continental flood basalts (CFBs) of Jurassic age make up the Vestfjella mountains of western Dronning Maud Land and demonstrate an Antarctic extension of the Karoo large igneous province. A detailed geochemical study of the 120-km-long Vestfjella range shows the CFB suite to consist mainly of three intercalated basaltic rock types designated CT1, CT2 and CT3 (chemical types 1, 2 and 3) that exhibit different incompatible trace element ratios. CT1 and CT2 of north Vestfjella record wide ranges of Nd and Sr isotopic compositions with initial εNd and εSr ranging from +7·6 to −16·0 and −16 to +65, respectively. The southern Vestfjella is dominated by CT3 with near-chondritic εNd (+2·0 to −4·1) and εSr (−11 to +19). A volumetrically minor suite of ocean island basalt (OIB-)like CT4 dykes (εNd +3·6, εSr +1) cuts the lava sequence in north Vestfjella. The pronounced isotopic differences suggest different magmatic plumbing systems for the heterogeneous CT1 and CT2 suites and the relatively homogeneous CT3 lavas. This is further supported by the palaeoflow directions, which point to major source regions to the north (CT1 and CT2) and east (CT3) of Vestfjella. These source regions can be associated with two contemporaneous major lithospheric thinning zones that permitted magma emplacement and controlled the melting of upper-mantle sources in the Jurassic Dronning Maud Land. The CT1 and CT2 magmas utilized the northern zone of thinning and were emplaced into the 3 Ga Grunehogna craton, whereas the CT3 magmas were emplaced through thinned Proterozoic Maud Belt lithosphere. Trace element and isotopic studies of the identified magma types reveal a complex history of fractionation and contamination at different lithospheric levels. All extrusive rock types show evidence of crustal contamination but this had rather small impact on their diagnostic trace element ratios. Much stronger overprint, in the CT1 and CT2 suites, resulted from contamination with veined Archaean lithospheric mantle, which produced wide ranges of isotopic and highly incompatible element ratios. CT3, in turn, does not show evidence of interaction with the Proterozoic lithospheric mantle. The high-εNd endmembers of CT1, CT2 and CT3 probably closely resemble uncontaminated mantle-derived magmas and indicate three different mantle sources. The CT2 primary magmas were derived from light rare earth element (LREE)-depleted, slightly large ion lithophile element (LILE)-enriched sources, whereas data on the volumetrically preponderant CT1 and CT3 point to variably LREE-enriched, strongly LILE-enriched sources. The sources of CT1, CT2 and CT3 may record large-scale lateral heterogeneity generated by subduction-contamination of the Gondwanan upper mantle. The OIB-like CT4 dykes probably reflect asthenospheric heterogeneities that were unrelated to the proposed subduction-contamination.
Keywords: Dronning Maud Land; geokjemi; geologi; petrografi; petrologi

Geochemistry of basalt lavas from Vestfjella and adjacent areas, Dronning Maud Land, Antarctica - Furnes, Harald; Vad, Erik; Austrheim, Håkon; Mitchell, John G.; Garmann, Leif B. (Lithos, 1987)
K-Ar ages, major- and trace-element compositions, and Sr-isotope data are presented for basalt lavas from Vestfjella, Dronning Maud Land, Antarctica. The new conventional K-Ar age data have yielded ages from 171 ± 2 to 695 ± 11 Ma, but the youngest (i.e. Middle Jurassic) ages are preferred. Mineralogical and chemical data show that the majority of the basalts are tholeiites. Petrographic mixing calculations, REE modelling, and the Sr isotope data suggest that they were derived by partial melting of garnet-free lherzolites with variable REE patterns, and subsequently modified by fractionation of olivine, Ca-rich pyroxene and plagioclase. Incompatible trace-element data from nearby Middle Jurassic basalt lavas (from Kirwanryggen and Heimefrontfjella) suggest a different source and REE modelling indicates generation from garnet lherzolites.
Keywords: Dronning Maud Land; NARE 1976/77; geokjemi; geologi; mineralogi; paleontologi; petrografi